PENINGKATAN KEMAMPUAN BERPIKIR MATEMATIS SISWA PADA MATERI BANGUN DATAR MELALUI MODEL PEMBELAJARAN PROYEK TERINTEGRASI STEM - Indriani, Kanti warih ade (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The problem of students' difficulties on shapes material (triangles) becomes the background of the researcher to carry out research using a project learning model that is integrated with the STEM approach. The purpose of research is to improve students' mathematical thinking abilities. The research subjects were students of class VIII SMPN 4 Taliwang. The instruments used were observation sheets and tests. In STEM-learning projects, students are trained to solve mathematical problems through projects that are integrated with other fields of science. This research is a classroom action research conducted in 2 cycles. Each cycle is carried out with 4 stages, namely planning, action, observation, and reflection. The results showed that the mathematical ability of students in cycle 1 achieved an average score of 72 with a classical completeness of 70%, increasing in cycle 2 achieving an average score of 80 with a classical completeness of 83%. Based on these data it can be concluded that through the application of the project learning model integrated STEM can improve students' mathematical thinking abilities on flat build material in class VIII SMPN 4 Taliwang